A study on space and facilities management in public school (special education integration program in Klang Valley) / Siti Aishah Maseroo - Maseroo, Siti Aishah (2011)
Every student in our country has equal opportunities to education irrespective of age, gender, or race. National Education Policy of students who want advanced in terms of intellectual, spiritual and physical, emotional and social need for students to develop their potential. There are groups of students labeled as special or exciting line of students. This students should be given attention and encouragement in order to contribute to become a nation of a normal student. Accordingly, the Ministry of Education Malaysia has produced a plan that documented as the Education Development Master Plan (EDMP, 2001). EDMP aims to ensure every citizen to gain access to education for 12 years of convenience, equity and quality. The Ministry of Education Malaysia (MOE) has established several schools Special Education for children with special needs and increasing integration programs in ordinary school. MOE sought to increase educational services for children with special needs not only special in terms of quantity but also quality (MOE, 2001). This study was conducted for the purpose of review proceedings of area management practiced and obstacles faced by special students and teachers during the process of learning and teaching in the Special Education Integration Programme (SEIP) with learning disabilities in the Klang Valley. The intent of this project to identify and wherever possible to make recommendations to help teachers to dispelling the capabilities and expertise in performing the duties of special education with learning disabilities by providing facilities and space for teaching and learning process to improve educational performance. The role of teachers in dispelling the capabilities and expertise in performing the duties of disable pupil is notably significant. It became key success factors and direct impact towards the space and management facilities at special integrated schools. There are a few significant findings based on questionnaires analysed and interview with respondents. Until quite recently most architects and designers had shown little understanding of the problems to impaired people. Extensive research need to be done as far as personal technical aids are concerned to improve the physical environment.